Designing STEM–based Learning Management System using Moodle as a Distance Learning Alternative in Basic Calculus Courses - Ibrahim, Malik; Sunardi, Sunardi; Isnaini, Lalu Moh Yudha (Universitas Muhammadiyah Mataram, 2022)
This study aims to develop STEM-based Learning Management System using Moodle as an alternative to distance learning in a structured manner. ADDIE method deploy as the development model and outlined in the Moodle-assisted platform. Product quality Measurement using questionnaires, by looking at the percentage of user response. The study found that; (1) the expert validation of the STEM-based Learning Management System using Moodle is 3,76 which is converted to 94%, (2) the practicality of STEM-based Learning Management System is 3,83 which is converted to 95,75%, (3) STEM-based LMS gave positive result by easy to use and has a service menu that is served clearly to student with a total value of 3,84 converted to 96%. The STEM based LMS effectively used during the covid 19 pandemic as an alternative to distance learning, and has an impact on problem-solving capabilities.